A regional development index for Portugal - Silva, R.; Ferreira-Lopes, A. (Social Indicators Research, 2014)
In a report from 2008 the Organization for Economic Cooperation and Development (OECD) came to the conclusion that Portugal is a country still very much marked by regional asymmetries and in need of better regional governance mechanisms and policies. We propose a regional development index for Portugal at the NUTS III level, based on the methodology of the Human Development Index (HDI) from the United Nations Development Programme (UNDP), which will be helpful to assess the evolution of the asymmetries between regions and evaluate the need for regional policy. Results show us a country that has most of the highest ranked NUTS III regions positioned along the coastline, although some interior NUTS III regions improved their relative positions in the ranking between 2004 and 2009. In addition to the three traditional dimensions of the HDI – income, education, and health - we include two more, given their increasing importance in the literature that criticizes the HDI and suggests the inclusion of new variables - governance and environment. Results show some considerable differences when we add the environment dimension: the interior regions improve their relative positions in the ranking, but in terms of governance they change little. Results also show that there is still the need for regional policy, although the dispersion in the ranking between the best and worst positioned NUTS III regions has decreased in all dimensions except education.